2006
DOI: 10.1080/09723757.2006.11885946
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Castes and Tribes of India: Glucose-6-Phosphate Dehydrogenase Deficiency and Abnormal Haemoglobins (HbS and HbE)

Abstract: The discipline of Biological Anthropology (or Human Biology) incorporates study of biology and environmental factors, as well as the forces of micro-evolution leading to macro-evolution, which ultimately influences the structure of human populations. In the present paper and attempt has been made to study the distribution of Glucose-6-Phosphate Dehydrogenase Deficiency and Abnormal Haemoglobins (HBS and HBE) frequencies among the people of India, which are analysed in relation to ecological, socioeconomic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…A higher prevalence of G6PD deficiency (number evaluated) was observed in the east (6.7%, N = 2,899), central (6.1%, N = 329), and north (5.8%, N = 9,772) of India compared with the west (4.1%, N = 17,575) and south (3.2%, N = 8,908), where it is mainly confined to Andhra Pradesh and Tamil Nadu 28. For ethnic groups, the frequency was highest in scheduled tribes (5.5%, N = 5,468) and community (4.9%, N = 22,790) compared with caste (3.6%, N = 5,303) and scheduled castes (2.7%, N = 5,922) 28. However, these proportions vary greatly depending on region, for example in north India the prevalence of G6PD deficiency is 6.6% in the caste group.…”
Section: Chemotherapymentioning
confidence: 96%
See 2 more Smart Citations
“…A higher prevalence of G6PD deficiency (number evaluated) was observed in the east (6.7%, N = 2,899), central (6.1%, N = 329), and north (5.8%, N = 9,772) of India compared with the west (4.1%, N = 17,575) and south (3.2%, N = 8,908), where it is mainly confined to Andhra Pradesh and Tamil Nadu 28. For ethnic groups, the frequency was highest in scheduled tribes (5.5%, N = 5,468) and community (4.9%, N = 22,790) compared with caste (3.6%, N = 5,303) and scheduled castes (2.7%, N = 5,922) 28. However, these proportions vary greatly depending on region, for example in north India the prevalence of G6PD deficiency is 6.6% in the caste group.…”
Section: Chemotherapymentioning
confidence: 96%
“…For the regions considered in more detail, the estimated prevalence of G6PD deficiency was 4.2% for Gujarat ( N = 1,473), 2.0% for Haryana ( N = 49), 0% for Karnataka ( N = 87), and 1.1% for Odisha ( N = 200) 28. Given that in 2006 when this analysis was performed, the population of these regions exceeded 160 million, the lack of data on G6PD deficiency prevalence in India is clear.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…18 The prevalence in Assam as found by Bhasin in 2006 is 8.8%. 19 A study conducted in Manipur in 2010 by Achoubi among the different communities found high prevalence among the Manipuri Muslims (21.32%) followed by the Brahmins (9.45%) and Kabui (7.84%). 20 In Mizoram also, a high prevalence of 17.5% was found in the population.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of G6PD*def in India varies from complete absence among the Ganchha of Rajasthan (Choubisa, 1985) to 0.271 among the Nagas of Nagaland (Bhasin, 2006).…”
Section: Introductionmentioning
confidence: 99%